(untitled) (Global Journal of Management and Business Research, 2022)
The inclusion of rural women in the formal banking sector is not considered as a final goal in itself for this study but it is a necessary condition for the transition of rural women from a state of poverty and destitution to a status of sufficiency This study aimed to measure the ability of microfinance projects borrowed by rural women from the Gadarif Microfinance institution GMI during the study period 2014-2020 with the objective of integrating them into the official banking system For this purpose a mixed approach was used in data collection and analysis including both quantitative and qualitative approaches The study concluded that aforesaid microfinance projects did not contribute to the integration of rural women into the formal banking sector in Gadaref State - Sudan This result attributed to many factors namely the macroeconomic factors related to economic stability and other factors related to banking policies whether at the level of financial institutions or financial decision-makers beside other cultural and social factors related to rural women and their local communities